2015
DOI: 10.4178/epih/e2015052
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection and risk of lung cancer in never-smokers and women: an ‘adaptive’ meta-analysis

Abstract: OBJECTIVES:The incidence of lung cancer in Koreans is increasing in women and in both men and women with a never-smoking history. Human papillomavirus (HPV) infection has been suggested as a modifiable risk factor of lung cancer in never-smokers and women (LCNSW). This systematic review (SR) aimed to evaluate an association between HPV infection and lung cancer risk in LCNSW.METHODS:Based on a prior SR and some expert reviews, we identified refereed, cited, or related articles using the PubMed and Scopus datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
(53 reference statements)
1
24
0
1
Order By: Relevance
“…Jong-Myon Bae associate HPV with lung cancer in non-smokers and women in Korea and recommend preventation (14).…”
Section: S S U E 2 2 0 1mentioning
confidence: 99%
“…Jong-Myon Bae associate HPV with lung cancer in non-smokers and women in Korea and recommend preventation (14).…”
Section: S S U E 2 2 0 1mentioning
confidence: 99%
“…One of them included longitudinal studies: a nested case-control and a cohort study with high causality [24]. According to subgroup analyses from several trials, the HPV infection constitutes a risk for lung cancer, especially in non-smokers, similar to the findings in head and neck cancers, females and Asian race [22,24,82]. Additionally considering HPV affinity to squamous cells, HPV infection constitutes a risk for squamous cell lung cancer; however, other histologic subtypes including ADC and SCLC have also been related to HPV infection [23,24,94].…”
Section: Hpv In Lung Cancer Clinical Information and Perspectivementioning
confidence: 96%
“…Likewise, recent studies have demonstrated a significantly increased risk of acquiring lung cancer in non-smokers who are exposed to HPV infection (OR 5.32; 95% CI 1. 75-16.17) [22,23]. Figure 1 depicts a meta-analysis of recent studies evaluating the association between HPV infection and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…An “adaptive” meta-analysis also revealed a significant effect of HPV infection in lung cancer risk in East Asian women and never smokers [34]. …”
Section: Non-smoking East Asian Female Lung Adenocarcinomamentioning
confidence: 99%